Perubahan Organisasi Dengan Pendekatan Diagnosa Pestle Model Pada Bank X: Organizational Change With Pestle Model Diagnosis Approach At Bank X - MJP, Arif Wibisana; Kadiyono, Anissa Lestari (Efektor, 2023)
This study aims to analyze the condition of Bank. X as the basis for carrying out steps for changing and developing the organization of Bank X in the future uses the PESTLE model analysis. Researchers conducted interviews with 1 Brand Manager and distributed questionnaires to 3 employees of Bank X. The results of the study indicate that there are several changes that are felt directly or indirectly by the company. Changes that occur and must be obeyed by Bank. X is a change in the law or law so that there are so many regulations and they change every year or even every month. However, sometimes some of these regulations hinder the achievement of employee targets/KPIs. Therefore some employees refuse to change according to current regulations. That way the advice that can be given to Bank X is a curative intervention that aims to make employees accept any changes that occur. Employees are given awareness to accept that regulations from Bank Indonesia and OJK must be followed.